Peran Syaikh Abubakar Abdullah (Datuk Gunung Tajam) Dalam Penyebaran Islam Di Pulau Belitung - Anwar, Saiful (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2024)
Islam first entered the Bangka Belitung Islands from Johor in the 16th century AD. The process of entering Islam into the island of Bangka was inseparable from the entry of merchant ships of the Johor sultanate, the Minangkabau kingdom, and Banten, then continued during the Palembang Sultanate, the VOC and the Dutch colonial rule. In connection with the spread of Islam in Belitung Island, there were seven spreaders of Islam. The seven propagators of Islam are better known to the public as Datuk Keramat. Among them are Datuk Gunung Tajam. However, in this article there is absolutely no definite record of the entry year of the seven sacred datuk and how the method of spreading Islam by the seven datuk from Aceh. In addition, the article also does not describe the social conditions, especially related to the local community worship practices that were developing at that time.